Helminth parasites of Mabuya arajara Rebouças-Spieker, 1981 (Lacertilia: Mabuyidae) from Chapada do Araripe, northeastern Brazil - Cabral, Arthurdo Nascimento (2018)
We provide data on the helminth fauna from the digestive tract of the lizard Mabuya arajara Rebouças-Spieker, 1981 from Chapada do Araripe, northeastern Brazil. Seventy one of the 127 lizards examined (56%) were infected with four nematode species: Physalopteroides venancioi and Physaloptera sp. (Physalopteridae), Strongyluris oscari (Heterakidae), and Parapharyngodon alvarengai (Pharyngodonidae), the latter being the component species (prevalence 53.5%; mean intensity of infection 3.37 ± 2.0; discrepancy index D = 0.69). The helminth P. alvarengai infected M. arajara throughout the year and showed increased infection rates in July, at the beginning of the dry season. In addition to the relationship with seasonality, lizards with greater body length and/or body mass were more infected. Relationships between number of parasites and body mass and with the sexes of lizards, on the other hand, were not found. Mabuya arajara represents a new host for these nematodes. This study contributes to the knowledge of the helminth fauna associated with the digestive tract of lizards from South America and the Caatinga domain.